2015
DOI: 10.1186/s12913-015-0752-0
|View full text |Cite
|
Sign up to set email alerts
|

How much of the productivity losses among psoriasis patients are due to psoriasis

Abstract: BackgroundIn previous studies, productivity losses have been measured specifically due to psoriasis or generally due to health problems in psoriasis patients. There is no information on the proportion of health related productivity losses that are due to psoriasis.The aim of this study was to estimate the proportion of productivity losses due to psoriasis and due to other medical problems among employed psoriasis patients.MethodsPatients visiting a tertiary level dermatological clinic during a one-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…In addition, the time cost was not transformed to monetary costs, and earlier studies have shown that the burden of phototherapy falls on the patient and employee, who both may pay marked time-related cost. 45,46 We were able to show that NB-UVB phototherapy works well in a normal clinical setting and both psoriasis and AD patients showed highly significant alleviation of their skin conditions and improvement of their HRQoL. The improved situation, as seen in disease scores, global measures, and DLQI, was sustained in both patient groups for at least 3 months confirming that earlier research outcomes coincide with clinical outcomes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the time cost was not transformed to monetary costs, and earlier studies have shown that the burden of phototherapy falls on the patient and employee, who both may pay marked time-related cost. 45,46 We were able to show that NB-UVB phototherapy works well in a normal clinical setting and both psoriasis and AD patients showed highly significant alleviation of their skin conditions and improvement of their HRQoL. The improved situation, as seen in disease scores, global measures, and DLQI, was sustained in both patient groups for at least 3 months confirming that earlier research outcomes coincide with clinical outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…The low figures (Appendix ) did not mean that there was a shortage of patients, but rather that there was not enough staff or time to complete the study in a busy clinic. In addition, the time cost was not transformed to monetary costs, and earlier studies have shown that the burden of phototherapy falls on the patient and employee, who both may pay marked time‐related cost …”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity highly influences the total morbidity, healthcare costs and socioeconomic burden of psoriasis. It has been estimated that a third of productivity losses in psoriasis patients are attributed to psoriasis while comorbidity accounts for the rest [44]. We suggest that addressing comorbidities early and working with prevention are beneficial not only for patients but also a valuable investment for the society as a whole.…”
Section: Discussionmentioning
confidence: 91%
“…Quality of life has been extensively investigated, and numerous studies have revealed a negative impact of the disease on this parameter . The professional activity of patients with psoriasis, assessed from their professional status or work productivity and activity impairment, has already been studied in several surveys, but in the absence of a control group, the specific consequences of the disease could not be measured . Moreover, these studies did not usually take account of the subgroup of patients with psoriatic arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…8 The professional activity of patients with psoriasis, assessed from their professional status or work productivity and activity impairment, has already been studied in several surveys, but in the absence of a control group, the specific consequences of the disease could not be measured. 6,[9][10][11][12][13][14][15][16][17][18][19] Moreover, these studies did not usually take account of the subgroup of patients with psoriatic arthritis. The objective of the PsoPRO (Psoriasis & PROfessional life) survey was therefore to assess the impact of psoriasis on professional life in France by comparing the working population of psoriasis patients with control subjects without the disease.…”
Section: Introductionmentioning
confidence: 99%